2019
DOI: 10.1002/hbm.24550
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal neuroimaging analysis reveals age‐associated common and discrete cognitive control constructs

Abstract: The aims of this study were to determine which cognitive control functions are most sensitive to cross‐sectional age differences and to identify neural features in different neuroimaging modalities that associated cognitive control function across the adult lifespan. We employed a joint independent component analysis (jICA) approach to obtain common networks among three different brain‐imaging modalities (i.e., structural MRI, resting‐state functional MRI, and diffusion tensor imaging) in relation to the cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 104 publications
(163 reference statements)
1
15
0
Order By: Relevance
“…Specifically, frontal GM volume reductions play a role in mediating changes in age-related general elements of EF. These putative mechanisms also clarify our earlier work 35 , which found that joint components in the frontal regions contributed to the age-related common cognitive control construct.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Specifically, frontal GM volume reductions play a role in mediating changes in age-related general elements of EF. These putative mechanisms also clarify our earlier work 35 , which found that joint components in the frontal regions contributed to the age-related common cognitive control construct.…”
Section: Discussionsupporting
confidence: 86%
“…We selected our EF tasks based on Miyake's model, which distinguishes three EF components 3,4,6,44,45 : common EF, updating-specific EF, and shifting-specific EF. This study attempted to extend our recent study 35 showing significant correlations among EF, the frontoparietal cortices, and age. Specifically, we sought to determine whether the structural and network properties of the frontoparietal cortices mediate age-related changes in EF and, further, to determine whether the mediation effect was selective for a specific EF component or whether it was a generalized pattern for all EF components.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations